Weed Control in Beets - William M. Stall (EDIS, 2003)
Beets can be found as red beets, table beets or garden beets. Both the tops (greens) and the bottoms (swollen hypocotyle) may be eaten. Always check the label on beet greens because residue establishment varies. Clopyralid (Stinger) has just received labeling for use postermergence, over-the-top of beets. At the present time however, Stinger may not be sold in Florida. This may change in the future, so check labeling in Florida. This document is HS188, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2003.